Sedentary behaviour in a sample of south african office-based workers - Phaswana, Merling (University of the Witwatersrand, Johannesburg, 2024)
Background Sedentary behaviour is associated with cardiometabolic diseases amongst office- bound workers, primarily through extended sitting and engaging in low-energy- demanding activities during work hours. Similar to developed countries, South African workplaces are experiencing an increasing prevalence of obesity and related cardiovascular diseases, with sedentary behaviour and physical inactivity being the main contributors. However, there is limited data on the effectiveness of sedentary behaviour strategies in improving South African office-based workers' cardiometabolic risk markers. Objectives This study aims to assess the effectiveness of the height-adjustable sit-to-stand work on cardiovascular parameters in a cohort of office-based workers and to explore the perceptions of these workers about the feasibility and suitability of this intervention to reduce occupational sitting time. Methods A mixed-methods study design was used on office workers from the University of the Witwatersrand and a credit bureau company in South Africa. The qualitative papers used in-depth semi-structured interviews to explore office-based workers' perceptions and experiences using sit-to-stand workstations. The interview audio was recorded audio using Microsoft Teams (version 11, Microsoft Way, United States) and Phillips (DVT4010 Voice Tracer, Vienna, Austria). All transcripts were checked against the recordings to verify accuracy and credibility, and grammatical editing was adopted where necessary. For quantitative measures, participants were randomised into an intervention or control group to collect measures at baseline and 12 weeks in a cohort of South African desk-based workers. These biomarkers include anthropometry, sedentary behaviour and physical activity, sleep duration, blood pressure, glucose, glycated haemoglobin (HbA1c) and lipid profile. The cross- sectional paper quantified sedentary behaviour, overall physical activity, and the association with select cardiometabolic risk factors. The randomised control trial evaluated the short-term effects of height-adjustable sit-to-stand workstations on cardiometabolic risk markers. Descriptive and inferential statistics were used to describe and compare baseline and follow-up changes in the intervention. Results The height-adjustable sit-to-stand workstation was deemed feasible and well-accepted by our participants. Participants expressed that it motivated them to stand up and work and effectively alleviated discomfort associated with prolonged sitting. Most (68.0%) of the study participants were women, with a mean age of 40.2 ± 9.3 years. Our participants spend an average of 8 to 10 hours in sedentary behaviour. Both systolic (β: -0.234, p = 0.037 mmHg) and diastolic blood pressure (β: -0.250, p <0.001 mmHg) were inversely associated with accelerometery-measured light physical activity. However, there was no relationship between accelerometery- measured sedentary behaviour and cardiometabolic risk factors after analysis. The 12-week randomised control trial showed small improvements with blood pressure - 0.26 (d =1.10 mmHg) and Light physical activity -0.26 (d=3.57 min/day). We observed trivial effects, with most of our cardiometabolic outcomes including body mass index (BMI) -0.11 (d=1.07 kg.m2). Most participants withdrew early from workplace intervention due to the design and functionality of the height-adjustable sit-to-stand workstation. Conclusions This study adds to the limited evidence on environmental workstation modifications for reducing sedentary behaviour. Our findings show that South African office workers spend a substantial amount of time sitting during work hours and support the need for public health workplace interventions to mitigate the potential health risks associated with such sedentary behaviour. This study confirms that short-term height-adjustable sit-stand interventions effectively reduce workplace sitting time and promise to improve cardiometabolic health outcomes, suggesting that clinically significant effects might be noticed in long-term interventions. Therefore, future studies should consider individual preferences, workstation design, functionality, education, and motivation to ensure successful implementation, utilization, and compliance with sit-to-stand workstations
A thesis is submitted in fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Therapeutics Sciences, University of the Witwatersrand, Johannesburg 2024
Keywords: Sedentary behaviour; Physical activity; Cardiometabolic outcomes; Height adjustable sit-to-standworkstation; UCTD; SDG-3: Good health and well-being